2021
DOI: 10.3390/su13115946
|View full text |Cite
|
Sign up to set email alerts
|

Did Noise Pollution Really Improve during COVID-19? Evidence from Taiwan

Abstract: Background and objectives: The impacts of COVID-19 are like two sides of one coin. During 2020, there were many research papers that proved our environmental and climate conditions were improving due to lockdown or large-scale restriction regulations. In contrast, the economic conditions deteriorated due to disruption in industry business activities and most people stayed at home and worked from home, which probably reduced the noise pollution. Methods: To assess whether there were differences in noise polluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…WRST is a popular nonparametric test and is used widely in engineering, environmental, and medical etc. [40,41]. For all analyses, (p < 0.05) is considered significant and the results are shown in Table 5.…”
Section: Pearson Correlationmentioning
confidence: 99%
“…WRST is a popular nonparametric test and is used widely in engineering, environmental, and medical etc. [40,41]. For all analyses, (p < 0.05) is considered significant and the results are shown in Table 5.…”
Section: Pearson Correlationmentioning
confidence: 99%
“…The lockdown brought about drastic impacts at social and economic fronts [28][29][30][31] as well as impacts on the environment, particularly in the context of air quality, environmental, and noise reduction [32][33][34]. To date, previous data and studies have shown that the emergency measures taken by the government to prevent human activities in the lockdown period of COVID-19 had effectively and significantly reduced ambient air pollution [20,[35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The geospatial analysis by GIS technology is one of the important and effective methods for determining emissions of pollutants into the air. At the heart of statistical processes, the regression and estimation models are decision-making tools [46].…”
Section: Discussionmentioning
confidence: 99%